2017
DOI: 10.12973/iji.2017.10420a
|View full text |Cite
|
Sign up to set email alerts
|

Examining Ethnocentrism, Emotionalization, and Life Syllabus in Foreign Language Achievement

Abstract: Given the importance of ethnocentrism in social interactions and its influence on language learning and teaching, the present study intends to explore the possible relationships between using life syllabus and emotionalization on ethnocentric views using the foreign language achievement (FLA) scores. To this end, 273 Iranian English learners from different language institutes completed the scales. Structural equation modelling (SEM) was utilized to examine the possible interactions. The findings indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Additionally, the reviewed studies in English language teaching revealed that emotioncy has received more attention than the other five fields. The researched topics ranged from language skills (i.e., willingness to read, willingness to communicate, readability measurement, vocabulary retention) (see Pishghadam and Shayesteh, 2016 ; Shahian et al, 2017 ; Borsipour et al, 2019 ; Makiabadi, 2020 ) to life syllabus (Shakeebaee, 2020 ), emotionalization (Shakeebaee et al, 2017 ), teacher emotional labor and teacher burnout (Momenzadeh, 2020 ), test bias (Pishghadam et al, 2017a ), emo-sensory capital (Pishghadam et al, 2018a ) and Emotion-based language instruction (Pishghadam et al, 2013 ). There is abundant room for future studies on other areas of English language teaching, particularly other language skills, in light of emotioncy study.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the reviewed studies in English language teaching revealed that emotioncy has received more attention than the other five fields. The researched topics ranged from language skills (i.e., willingness to read, willingness to communicate, readability measurement, vocabulary retention) (see Pishghadam and Shayesteh, 2016 ; Shahian et al, 2017 ; Borsipour et al, 2019 ; Makiabadi, 2020 ) to life syllabus (Shakeebaee, 2020 ), emotionalization (Shakeebaee et al, 2017 ), teacher emotional labor and teacher burnout (Momenzadeh, 2020 ), test bias (Pishghadam et al, 2017a ), emo-sensory capital (Pishghadam et al, 2018a ) and Emotion-based language instruction (Pishghadam et al, 2013 ). There is abundant room for future studies on other areas of English language teaching, particularly other language skills, in light of emotioncy study.…”
Section: Resultsmentioning
confidence: 99%